The International ‘Balint’ Award – a rising opportunity for Romanian Medical Students - Lală, A (Carol Davila University Press, 2010)

(untitled)
The International ‘Balint’ Award for students, instituted by the Foundation for Psychosomatic and Social Medicine in honor of Michael and Enid Balint, has been a rising opportunity for Romanian medical and psychology students to achieve international fame. Romanian students have been among the winners of this award for the last 10 years, in competition with students from Ivy League and other illustrious universities. The ‘Ascona model’ case presentation debates the psychological side of a medical case, while keeping in focus the diagnostic, pathology and treatment issues. This article focuses on explaining this type of case presentation in correlation with one of the papers submitted in the contest that has received this award in the 15(th) International Balint Congress. The exposed case is that of a 17–year–old boy presenting with apparent stupor encountered by an emergency mobile unit. The patient was suspected of substance abuse and overdose but these suspicions were denied by the clinical exam. Further encounters led to the conclusion that both the boy and his whole family needed psychotherapy counseling and were referred there with great success.